Pore formation by human stefin B in its native and oligomeric states and the consequent amyloid induced toxicity - Anderluh, Gregor; Zerovnik, Eva (Frontiers in Molecular Neuroscience, 2012)
It is well documented that amyloid forming peptides and proteins interact with membranes and that this correlates with cytotoxicity. To introduce the theme we give a brief description of some amyloidogenic proteins and note their similarities with pore forming toxins and cell penetrating peptides. Human stefin B, a member of the family of cystatins, is an amyloidogenic protein in vitro. This review describes our studies of the interaction of stefin B oligomers and prefibrillar aggregates with model membranes leading to pore formation. We have studied the interaction between human stefin B and artificial membranes of various compositions. We also have prepared distinct sizes and morphologies of stefin B prefibrillar states and assessed their toxicity. Furthermore, we have measured electrical currents through pores formed by stefin B prefibrillar oligomers in a planar lipid bilayer setup. We finally discuss the possible functional and pathological significance of such pores formed by human stefin B.